The Role Of IPSAS In Controlling Corruption Of Emerging Country : Study In Indonesia - Andi Nur Sakinah; Haliah Haliah; Andi Kusumawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the role of IPSAS in increasing transparency and accountability to control corruption in developing countries such as Indonesia. This research uses descriptive analysis method with literature study approach. The implementation of IPSAS in Indonesia is the right step to take to control corruption that is currently rampant. This study analyzes that IPSAS can improve the quality of public sector financial reporting by creating transparency and accountability that can prevent fraud. However, to adopt IPSAS optimally, Indonesia needs to pay attention to the quality of its staff to be more competent, and improve its infrastructure.